Lipid Profile Abnormalities and Cardiovascular Risk among Hypertensive Patients in Al-Hussein Teaching Hospital in Al-Samawa, Iraq, 2023-2024 - Sahib, Bahaa Othman; Ali, Emad Baqer; Jasim, Mahmod S. (American Journal of Biomedicine and Pharmacy, 2026)
Background: Hypertension is a major public health challenge globally and in Iraq, serving as a primary risk factor for cardiovascular disease (CVD). The coexistence of dyslipidemia significantly amplifies this risk. Understanding the local pattern of lipid abnormalities and the aggregated cardiovascular risk is crucial for effective preventive strategies. This study aimed to assess the prevalence of lipid profile abnormalities and estimate the 10-year cardiovascular risk among hypertensive patients attending Al-Hussein Teaching Hospital in Al-Samawa, Iraq. Methods: A cross-sectional study was conducted at the outpatient cardiology clinic of Al-Hussein Teaching Hospital from January 2023 to December 2024. A total of 384 adult patients with a confirmed diagnosis of essential hypertension were enrolled. Data on sociodemographics, clinical characteristics, and lifestyle factors were collected through interviews and medical records. Fasting blood samples were analyzed for total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). The 10-year risk of fatal and non-fatal CVD was calculated using the WHO/ISH risk prediction charts for the Eastern Mediterranean Region. Statistical analysis was performed using SPSS version 26, with a p-value <0.05 considered significant. Results: The prevalence of dyslipidemia among hypertensive patients was 78.1%. The most common abnormality was low HDL-C (54.9%), followed by high LDL-C (48.7%), hypertriglyceridemia (41.1%), and hypercholesterolemia (35.9%). According to the WHO/ISH risk stratification, 28.9% of patients were in the high to very high 10-year CVD risk category (>20%). A significant association was found between increasing age, male gender, smoking, obesity, and higher CVD risk categories (p<0.05). Conclusion: Lipid profile abnormalities, particularly low HDL-C, are highly prevalent among hypertensive patients in Al-Samawa, leading to a substantial proportion being at high risk for future cardiovascular events. These findings underscore the urgent need for routine screening and integrated management of both blood pressure and lipid levels in this population to mitigate the burgeoning burden of CVD in Iraq.